Pertanggungjawaban Pidana bagi Pembuat Drug Design dalam Perspektif Hukum Narkotika - Aulia Rahma Sari (Faculty of Law, Universitas Airlangga, 2025)
The proliferation of technology has fueled the rise of drug abuse, giving rise to new modus operandi such as